FAIR PLAY AND THE LOGIC OF SPORT (Fiep Bulletin - online, 2012)
Fair play may range from rule-adherence to a general attitude towards sport (showingmodesty in victory and serenity in defeat, per example).This paper discusses fair play both in education and in competitions.According to the author, playing fairly is not simply playing morally. It is necessary toacknowledge the internal logic of sports. A good example is the thin line between deception andcheating: the first is usually accepted in sports when it is employed as a tactic which does not break arule.The rules and qualities of a game constitute a laboratory for the values experimentation; theycontinuously challenge our moral intelligence. How we respond will be part of our development.
Keywords: fair-play; ethics; sport values